(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the theoretical foundations of economic security within private enterprise, drawing upon insights from the resource-based view, dynamic capabilities perspective, institutional theory, and transaction cost economics. By examining these theoretical perspectives, the article elucidates the determinants, dynamics, and implications of economic security for firms’ strategies, operations, and performance. Through the integration of theoretical insights, firms can enhance their resilience, competitiveness, and long-term viability in an increasingly dynamic and competitive business landscape.